Penggunaan Metode Pembelajaran Demonstrasi pada Mata Pelajaran Pendidikan Agama Islam dalam Upaya Meningkatkan Hasil Belajar Siswa Kelas V.A SD Negeri 114/X Pandan Jaya - Sutiban Sutiban (Departement of Mathematics Education, 2021)
This study aims to disclose information and discuss the use of Demonstration Learning Methods in Islamic Religious Education Subjects in an Effort to Improve Student Learning Outcomes for Class V.A SD Negeri 114/X Pandan Jaya. This research is included in the type of classroom action research (CAR). This research was carried out in this research was carried out at SD Negeri 114/X Pandan Jaya. The time of this research was carried out in the odd semester of the academic year 2021 - 2022, which began in September 2021. The subjects in this study were class V.A students, totaling 25 people. The research procedure consisted of two cycles with four stages of research starting from planning, implementing, observing and reflecting. Data collection in this study was carried out using observation sheets, field notes, learning outcomes test sheets, and documents. The data were analyzed using the percentage formula.The results of this study indicate that through Demonstration Learning in Islamic Education Subjects can improve student learning outcomes in class VA SD Negeri 114/X Pandan Jaya which is marked by an increase from pre-cycle (20%), cycle I (60%), cycle II (80%).